2017
DOI: 10.1177/0264550517701200
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational offending

Abstract: Intergenerational offending refers to the observed phenomenon that offending tends to run in families. As small groups of families have been shown to be responsible for a considerable proportion of crime, there has been a substantial amount of effort expended in researching both the prevalence and patterns of such crime. The mechanisms by which intergenerational continuity of offending is generated, however, are not well understood. Perhaps more importantly, there is even less understanding about those factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Our findings regarding the transmission of offending from mothers to daughters are consistent with other studies, such as Auty et al (2017) and Tzoumakis et al (2020), both of whom identified stronger same-sex effects, which might be attributed in part to learnt gender roles. The lack of association between girls’ offending and the wider constellation of risk factors identified in other studies, such as growing up in poverty or other aspects of family dysfunction, could suggest that girls are more resistant to criminogenic environments than boys (an area of research that is highly under-developed according to Flynn et al, 2017). While out with the scope of this article, this might relate to gendered behavioural expectations learnt in childhood.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Our findings regarding the transmission of offending from mothers to daughters are consistent with other studies, such as Auty et al (2017) and Tzoumakis et al (2020), both of whom identified stronger same-sex effects, which might be attributed in part to learnt gender roles. The lack of association between girls’ offending and the wider constellation of risk factors identified in other studies, such as growing up in poverty or other aspects of family dysfunction, could suggest that girls are more resistant to criminogenic environments than boys (an area of research that is highly under-developed according to Flynn et al, 2017). While out with the scope of this article, this might relate to gendered behavioural expectations learnt in childhood.…”
Section: Discussionmentioning
confidence: 96%
“…While these four theoretical perspectives are not exhaustive, they do provide a useful framework by which to understand the most common hypotheses of intergenerational offending. However, on the important question of whether the effect of mothers is likely to differ from that of fathers, the research is ‘surprisingly limited’ (Besemer et al, 2016: 436), with existing theories predominantly based on studies of offending among fathers and sons (Flynn et al, 2017; Tzoumakis et al, 2020). This contrasts sharply with other disciplinary areas, such as child psychology and development, in which theories are dominated by studies examining the influence of mothers (Detweiler et al, 2010).…”
Section: Theoretical and Research Contextmentioning
confidence: 99%